Benefits of Helicobacter pylori Eradication on Extragastric Diseases - Tae Jun Kim; Hyuk Lee (Yong Chan Lee, 2021)
Helicobacter pylori (H. pylori) eradication can reduce the risk of gastric diseases such as gastritis, gastric ulcer, and gastric adenocarcinoma. Since H. pylori was discovered more than 30 years ago, many studies have reported associations between H. pylori infection and extragastric diseases such as immune thrombocytopenia and iron-deficiency anemia. Thus, recent guidelines recommended H. pylori eradication in patients with those diseases. In contrast, although the role of H. pylori eradication in other extragastric diseases remains controversial, there is growing evidence of its benefit on them, especially cardiovascular (ischemic heart disease and stroke), metabolic (dyslipidemia, diabetes mellitus, and non-alcoholic fatty liver disease), neurodegenerative (Parkinson's disease and Alzheimer's disease), autoimmune (Graves' disease, Hashimoto's thyroiditis, Raynaud's syndrome, rosacea, and chronic urticaria), and other (cap polyposis, colorectal mucosa-associated lymphoid tissue lymphoma, periodontal disease, hyperemesis gravidarum, and osteoporosis) conditions. A recent prospective randomized study reported that H. pylori eradication improved insulin resistance and dyslipidemia. These findings were consistent with the results of a recent meta-analysis. Therefore, well-designed prospective interventional studies are needed to examine the effects of H. pylori eradication on various extragastric diseases.